Manual reduction and splint fixation for distal radius fracture with dislocation: a case report - Zhu, Wensheng; Tu, Shuangqiang; Zhu, Hairui; Shan, Feng (Frontiers in Surgery, 2025)
IntroductionDistal radius fractures (DRF) are one of the most common fractures, accounting for approximately 20% of all fractures. DRF is frequently associated with distal radioulnar joint (DRUJ) dislocation, which may be initially overlooked due to subtle symptoms and imaging findings. This can lead to misdiagnosis and suboptimal treatment.Patient concernsAn elderly female patient presented with a distal radius fracture. Early clinical and imaging evaluations failed to identify a co-existing DRUJ dislocation.DiagnosisThe DRUJ dislocation was subsequently diagnosed after careful assessment, highlighting the need for a thorough examination in cases of DRF.InterventionsThe DRUJ dislocation was managed with manual reduction followed by splint fixation. The patient was closely monitored throughout the treatment process.OutcomesFollowing the intervention, the patient demonstrated significant functional recovery, with improvement in wrist mobility and reduction in pain.ConclusionThis case underscores the importance of early detection of DRUJ dislocation in patients with DRF to avoid misdiagnosis and prevent long-term wrist dysfunction. Timely and appropriate intervention can lead to substantial recovery.